Leadership Message in Buya Hamka Movie Season 1 (Semiotic Analysis of Leadership Message in Buya Hamka Movie Season 1) - Teddy Khumaedi Teddy Khumaedi (Program Studi Komunikasi dan Penyiaran Islam Fakultas Dakwah Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2025)
Humans were created by Allah on earth to be caliphs, therefore, humans must have the soul of a leader to be able to manage the environment, groups and even lead themselves. As time goes by, leadership messages can not only be obtained through Basic Leadership Training (LDK), but can also utilize technology such as mass media, one of which is communication media, namely film. Film is one of the mass media tools used to convey messages from sources to audiences. The aim of this research is to find out Roland Barthes' semiotic analysis which consists of Denotation, Connotation and Myth as well as what leadership messages are contained in the film Buya Hamka Season 1. The method used in this research is descriptive qualitative with Roland Barthes' semiotic approach. The results of this research show that the film Buya Hamka Season 1 has various signs regarding leadership, both in verbal and non-verbal forms. Each scene has various leadership messages which are reflected through dialogue or scenes carried out by the characters. These scenes provide leadership messages and the leadership style used by the character Buya Hamka. The conclusion of this research is that there are signs of denotation, connotation, and myth that contain leadership messages as well as democratic, charismatic, transformational and paternalistic leadership styles.